2017
DOI: 10.1681/asn.2016111220
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular APOL1 Risk Variants Cause Cytotoxicity Accompanied by Energy Depletion

Abstract: Population genetic approaches have uncovered a strong association between kidney diseases and two sequence variants of the gene, called risk variant G1 and variant G2, compared with the nonrisk G0 allele. However, the mechanism whereby these variants lead to disease manifestation and, in particular, whether this involves an intracellular or extracellular pool of APOL1 remains unclear. Herein, we show a predominantly intracellular localization of APOL1 G0 and the renal risk variants, which localized to membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 62 publications
9
104
1
1
Order By: Relevance
“…Building on APOL1's known trypanolytic activity, published in vitro evidence has suggested that variantdependent, autophagic, or cytotoxic cell death is responsible for progressive kidney disease. We did not detect variantdependent, differential cytotoxicity, findings which differ from several prior reports using HEK293 cells, 25,30,36,37 HEK293T cells, 38 or human podocytes. 26 The reasons that our data differ from earlier publications are unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Building on APOL1's known trypanolytic activity, published in vitro evidence has suggested that variantdependent, autophagic, or cytotoxic cell death is responsible for progressive kidney disease. We did not detect variantdependent, differential cytotoxicity, findings which differ from several prior reports using HEK293 cells, 25,30,36,37 HEK293T cells, 38 or human podocytes. 26 The reasons that our data differ from earlier publications are unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…16 When associated with plasma membranes in cells, some report variant APOL1s permit greater intracellular potassium depletion than reference APOL1. 30,38 However, we found no variant-dependent differences in the intracellular potassium loss and found comparable channel activity in cells expressing APOL1-G0 compared with those expressing APOL1-G2. We characterized the mechanism of K + efflux for the first time in mammalian cells and found APOL1-G0 and APOL1-G2 both had pH-sensitive, nonselective, cation channel activity, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 55%
“…Despite strong evidence establishing CKD risk as a recessive trait (a mode of inheritance more commonly associated with loss-of-function mutations), most studies examining the disease mechanism have concluded the APOL1 variants produce a new protein function and represent gain-of-function mutations (18,26,28,36,44,48,62). The proposed new function endowed by the variants results in cytotoxicity; however, details of the biochemical mechanism are not fully established.…”
Section: Gain-of-functionmentioning
confidence: 99%
“…Several groups have investigated the intracellular localization and function of APOL1 in kidney cells, with differing conclusions. APOL1 has previously been reported to localize to the ER, partially to mitochondria, as well as to endosomes, lysosomes, and autophagosomes (10,19,20). Interestingly, although APOL1 has been well-characterized as an extracellular HDL-associated molecule (21), a hypothesized role as an intracellular lipid-binding protein has not been demonstrated (10,19).…”
mentioning
confidence: 99%